Correlation of medial temporal lobe atrophy with seizures in Alzheimer’s disease and mild cognitive impairment: A case control study - Dhikav, Vikas; Duraisawmy, Sharmila; Anand, Kuljeet Singh (International Journal of Epilepsy, 2017)
Background Seizures are common accompaniment of neurodegenerative disease. Though, Alzheimer’s disease (AD) is the most common cause, but seizures also occasionally occur in mild cognitive impairment (MCI).Material & methods We studied patients of Subjective Memory Complaints coming to the Department of Neurology of a Tertiary Care Hospital in Northern India from July 2012 to July 2015. A total of 171 patients were studied. Those with a diagnosis of AD/MCI with seizures were taken for the current study. A total of 30 controls with chronic diseases were taken for comparison. Medial Temporal Lobe Atrophy (MTA) Rating was done using Sheleten’s Visual Rating Scale.Results A total of 256 patients were screened and 171 had dementia of Alzheimer’s type (n = 75; M:F = 60:15) and 96 patients had MCI (M:F = 76:20). The mean MMSE of those with AD was 18.5 ± 3.3 was and that of the MCI was 26.6 ± 2.4. A total of 9 cases with AD had seizures and 6 had seizures in MCI group (total n = 15). Moderately strong correlation was obtained between MMSE of AD patients having seizures and MTA scoring.Conclusions Seizures are common in dementia of Alzheimer’s type and not uncommon in MCI. They have the potential to worsen the cognitive profile of the patient and need attention in these patients.
Keywords: Alzheimer’s disease; Mild cognitive impairment; Predictors; Seizures; Medial temporal lobe atrophy